Técnicas de motivação para colaboração no Moodle IMD - Aires, Samanta; Leite, Jair C. (Anais do Workshop sobre Aspectos da Interação Humano-Computador na Web Social (WAIHCWS), 2017)
Many information systems have some embedded social interaction tools that allow users to interact with other. For instance, a review forum in an e-commerce system is an example of an interaction tool that can help users to share purchase experiences. Question and answer forums are another kind of tool where people can get helpful information to solve theirs problems. However, an important aspect to assure the usefulness of such tools is the motivation of the users to collaborate with others in such environments. In this paper, we investigate the application of motivation techniques to enhance users participation in a virtual learning platform. Our case study uses a customized implementation of the Moodle platform (Moodle IMD) that is used by students in an Information Technology course. Our solution includes the introduction of rewards and recognition mechanisms to motivate users. We have added reaction buttons to provide social recognition of activities and we also have implemented a ranking and a leaderboard to display how students participation are going in comparison with other ones. The partial results show that the student becomes more motivated to collaborate with their course partners. In a future study, we aim to evaluate how effective this collaboration is to improve learning.